Epigenetic modification does not determine the time of POU5F1 transcription activation in cloned bovine embryos. - Jafari, Shahram; Hosseini, Sayyed Morteza; Hajian, Mehdi; Forouzanfar, Mohsen; Jafarpour, Farnoosh; Abedi, Parvaneh; Ostadhosseini, Somayyeh; Abbasi, Hassan; Gourabi, Hamid; Shahverdi, Abdolhossein H.; Vosough, Ahmad Dizaj; Anjomshoaa, Maryam; et al. (Springer, 2011)
Purpose To investigate the effect of epigenetic modification on pattern, time and capacity of transcription activation of POU5F1, the key marker of pluripotency, in cloned bovine embryos.